PROSPECTS FOR THE CUSTOMS UNION IN TERMS OF MODERN THEORIES OF REGIONAL INTEGRATION - D. M. Ghazaryan (Модернизация, инновация, развитие, 2017)
Leading the trend of world development is globalization, which covers all areas of public life, including economic, and national economies poses more challenges, fi rst and foremost – ensuring competitiveness on a global scale, fi nd their own niche in the international division of labor.The development of the global trading system is characterized by two interrelated trends – the expansion of economic openness and the formation of trade unions, to ensure the most favorable terms of trade between the participating countries. The latest trend has led to the relevance of research topic "Prospects of Customs Union from the point of view of modern theories of regional integration."The integration processes taking place in the former Soviet Union in fact since joining the former Soviet republics of the status of independent states. Already in 1991. CIS was created, which brought together 12 post-Soviet countries (all former Soviet republics except the Baltic). Since then, the integration processes in the post-Soviet space are permanent, and therefore, we set a goal – to analyze the prospects of the Customs Union from the point of view of modern theories of regional integration.Notwithstanding that goal has led to the need to address a number of problems, namely:• consideration of the role and place of regional trade (economic) union, the importance of their experience, especially for developing countries and countries with economies in transformation;• justify the importance of the openness of the national economy to generate the preconditions for sustainable economic growth, determining the levels of trade (economic) integration;• analysis of modern views on the nature of regional integration;• consideration of the characteristics of individual regional trade and economic unions, including the Customs Union, and determine their place in the modern system of world trade.The study is based on the use of a systematic approach using historical and logical methods.The result of the study was the conclusion there is a positive relationship between foreign trade and economic growth of member countries of the regional unions, including TC and the EAEC; articulated position relative to the benefi ts and future economic and political prospects of the Customs Union and the Eurasian Economic Union.The theoretical signifi cance of the article is the novelty and the possibility of further study the relationship between economic and political prospects of the vehicle and the EAEC.